Sexualidade masculina, medicalização e virilidade: análise de discursos médicos e midiáticos na era pré e pós Viagra® no Brasil (1989-2018) - Fabichak, Cibele A (2021)
This research aims to examine the transformation of male sexuality, focusing on masculinity, virility and the male body through the medicalization of a sexual disorder, impregnated with stigmas, impotence, in the time frame from 1989 to 2018. The problematization is established from the contextualization of medical and media discourses that interconnect three dimensions: urology (medical science), the pharmaceutical industry (capital) and the media (means of diffusing the interaction of the first two with the target audience), with the launch of the cultural-marketing framework of the Viagra® product, in 1998, in Brazil. Thirty years after the “explosion of the will to know” about female sexuality, with the introduction of the contraceptive pill, in the 60s, medicine deals with the sexual and general health of men, through the launch of another “pill, the so called blue pill”, which approaches impotence from a new angle: it transforms any “failure” or absence of an erection, from youth to old age, into an organic disorder of erectile function. Under the Foucaultian formulation of bio power interconnected with the History of the Body, we intend to analyze textual and imaginary narratives generated before and after the introduction of the drug, in the limits between body, health, disease, aging and sexuality. It also seeks to understand its impacts on urology, as a medical specialty, in addition to identifying the construction of ideal health and virility as consumer goods. As for the methodology, this research analyzes, in an unprecedented way, diversified medical sources, such as the scientific programs of urological medical congresses, medical consensus on erectile dysfunction, promotional materials, visual aids, as well as media sources, such as cover articles from magazine and advertisements and advertising films produced under the sponsorship of the pharmaceutical industry